Natalizumab Discontinuation and Treatment Strategies in Patients with Multiple Sclerosis (MS): A Retrospective Study from Two Italian MS Centers. Issue 2 (December 2015) - Lo Re, Marianna; Capobianco, Marco; Ragonese, Paolo; Realmuto, Sabrina; Malucchi, Simona; Berchialla, Paola; Salemi, Giuseppe; Bertolotto, Antonio
Abstract Introduction Natalizumab (NTZ) discontinuation can be followed by multiple sclerosis (MS) disease reactivation. Currently no disease-modifying drug (DMD) has been shown to be able to abolish disease reactivation. The aims of the current study were: (1) to determine the frequency of MS reactivation after NTZ discontinuation; (2) to evaluate predictors of reactivation risk, and (3) to compare the effect of different treatments in reducing this risk. Methods Data from 132 patients with MS followed-up for 2 years before NTZ treatment and 1 year after interruption were collected from two Italian MS centers and retrospectively evaluated. Results Overall, 72 of 132 patients (54.5%) had relapses after NTZ discontinuation and 60 of 125 patients (48%), who had magnetic resonance imaging, had radiological reactivation. Rebound was observed in 28 of 132 patients (21.2%). A higher number of relapses in the 2 years before NTZ treatment, a longer washout period, and a lower number NTZ infusions correlated with reactivation and rebound. Untreated patients (n = 37) had higher clinical and radiological activity and rebound in comparison to patients receiving DMDs. Moreover, a lower risk of relapses was found in patients treated with second-line therapies (NTZ and fingolimod) than in those treated with first-line therapies (interferon beta, glatiramer acetate, teriflunomide, azathioprine). Interestingly, no disease reactivation in off-label treatment (rituximab, autologous hematopoietic stem cell transplantation) was observed. Conclusion NTZ discontinuation is a risk for MS reactivation and rebound. An alternative treatment should be promptly resumed mainly in patients with a previous very active disease course and with a shorter NTZ therapy. Second-line therapies demonstrate superiority in preventing relapses after NTZ discontinuation.